2008
DOI: 10.1111/j.1755-053x.2008.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Debt Issuance and the Historical Level of Interest Rates

Abstract: "Using a sample that comprises more than 14,000 new issues of corporate debt for the period 1970-2001, we examine the relation between debt issues and the level of interest rates relative to historical levels. Consistent with recent survey evidence, we find that companies issue more debt, more debt relative to investment spending, and more debt compared to equity when interest rates are low relative to historical rates. The effects continue to hold when we control for other variables that influence debt issuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 22 publications
12
49
0
2
Order By: Relevance
“…Our results also find, according to the pecking order theory, an inverse relationship between leverage with debt cost (Cuñat 1999;Barry et al 2008) and firm age (Michaelas et al 1999;Hall and Graham 2000;López and Sogorb 2008). As reported in many previous studies (Giannetti 2003;Chen 2004;Huang and Song 2006;Frank and Goyal 2009;Céspedes et al 2010;Chakraborty 2010;Kayo and Kimura 2010), our results revealed an inverse relationship between cash flow and indebtedness, thus supporting the theoretical framework proposed in the pecking order theory.…”
Section: Empirical Evidence and Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our results also find, according to the pecking order theory, an inverse relationship between leverage with debt cost (Cuñat 1999;Barry et al 2008) and firm age (Michaelas et al 1999;Hall and Graham 2000;López and Sogorb 2008). As reported in many previous studies (Giannetti 2003;Chen 2004;Huang and Song 2006;Frank and Goyal 2009;Céspedes et al 2010;Chakraborty 2010;Kayo and Kimura 2010), our results revealed an inverse relationship between cash flow and indebtedness, thus supporting the theoretical framework proposed in the pecking order theory.…”
Section: Empirical Evidence and Discussionsupporting
confidence: 76%
“…Then, an inverse relationship it is expected between debt cost and leverage. This kind of relationship is found in different papers (Cuñat 1999;Barry et al 2008). The proposed hypothesis is:…”
Section: Debt Costmentioning
confidence: 72%
See 2 more Smart Citations
“…Two types of proxies are used to represent this variable: dummies for credit ratings, and dummy for rated and non-rated firms. Barry et al (2008) argued that firms use more debt when present interest rate is lower than the historical interest rate. Higher inflation means paying lower to the lender at the time of inflation and real value of tax advantage which is higher at the time of inflation (Taggart, 1985) may result positive relationship between inflation and leverage under the prediction of Trade-off theory.…”
Section: Supply-side Factorsmentioning
confidence: 99%